Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (Briefing Paper, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.

The Hidden Life of Theories of Change - Ho, Wenny; Tamas, Peter; van Wessel, Margit (Hivos, 2020)
Theory of Change is thought to be very useful for learning and adaptive management of complex interventions such as advocacy. Nevertheless, the use of Theory of Change is also under critique. One common criticism is that Theory of Change is often used as a framework that fixes agreements rather than as a living, guiding tool that helps reflection and adaptation. However, while such criticism stresses forms of control, little research has looked at the way Theory of Change and advocacy practice relate. This is a pertinent issue considering that formally agreed Theories of Change and realities on the ground can be very different. This raises questions: Do advocates work in ways different from what Theory of Change states, and if so, how, and why? How does the way they strategize relate to formal Theories of Change? With what implications? In this brief, we explore these more hidden aspects of the life of Theories of Change.